Usain Bolt : my story : 9.58 : being the world's fastest man - Bolt, Usain, 1986-; Custis, Shaun (London : HarperSport, 2010)
Since the heady days of the Beijing Olympics in August 2008, Usain Bolt has lowered both the 100 metres and 200 metres world records. At a stroke the Jamaican has become the greatest sports star in the world. Learn what makes him tick, where he gets his motivation, and where he takes his inspiration.
The fastest man in the world -- Home -- Family -- Getting started -- New coach -- Getting serious -- Beijing calling -- On top of the world -- Homecoming -- Berlin and beyond -- My island in the sun -- Off the track -- Coping with fame -- Hot topic -- Striving for more -- Beyond my sport -- The future.
Keywords: Bolt, Usain, -- 1986-; Runners (Sports) -- Jamaica -- Biography